Energy policy in Singapore – emission modelling - Koh, Hock Yang (Nanyang Technological University, 2024)
Singapore’s energy sector faces the challenge of balancing energy security with environmental sustainability. This project explores the potential of emission reduction policies using PLEXOS, a widely used energy modelling software. The project involves a literature review which gathers energy policy data in Singapore, the development of emission models for various technologies within PLEXOS and an implementation and simulation of a specific emission reduction policy for Singapore’s energy sector which is the carbon pricing act. The report analyzes the impact of the chosen policy on emission levels, highlighting potential benefits and drawbacks identified through simulations. The results offer valuable insights for policymakers and stakeholders as they navigate the path towards a more sustainable energy future for Singapore.